Edukasi Covid-19 Berbasis Leaflet Terbukti Meningkatkan Kepatuhan Remaja dalam Menerapkan Protokol Kesehatan di Kota Ambon - Nenny Parinussa; Gledys Piliay (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of Coronavirus which is a health problem throughout the world. One of the reasons for the high number of COVID-19 cases is non-compliance in implementing health protocols, especially for teenagers. Objective: This study aims to determine the effect of health education on the transmission of COVID-19 through leaflet media on adolescent compliance with the COVID-19 protocol in Hunut Durian Patah Village, Teluk District, Ambon City. Methods: This research was a pre-experimental study with one group pretest-posttest design. The sampling technique was purposive sampling. Collecting data using questionnaires, observation sheets, and leaflets. Results: The results of the paired sample t-test showed that there was a difference in adolescent compliance in implementing health protocols between before and after being given health education, with p-value = 0.001. Conclusion: Health education using leaflets is effective in increasing adolescent compliance in implementing the COVID-19 health protocol.Keywords: COVID-19; obedience; leafletABSTRAK Latar Belakang: Coronavirus Disease 2019 (COVID-19) merupakan penyakit menular yang disebabkan oleh Coronavirus jenis baru yang menjadi masalah kesehatan di seluruh dunia. Salah satu penyebab tingginya kasus COVID-19 di antaranya adalah ketidakpatuhan dalam menerapkan protokol kesehatan, terutama para remaja. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan tentang penularan COVID-19 melalui media leaflet terhadap kepatuhan remaja menerapkan protokol COVID-19 di Desa Hunut Durian Patah, Kecamatan Teluk, Kota Ambon. Metode: Penelitian ini merupakan penelitian pra eksperimental dengan desain one group pretest-posttest. Teknik pengambilan sampel adalah purposive sampling. Pengambilan data menggunakan kuesioner, lembar observasi, dan leaflet. Hasil: Hasil paired aamples t-test menunjukkan adanya perbedaan kepatuhan remaja dalam menerapkan protokol kesehatan antara sebelum dan sesudah diberikan pendidikan kesehatan, dengan p-value = 0,001. Kesimpulan: Pendidikan kesehatan menggunakan leaflet efektif untuk meningkatkan kepatuhan remaja dalam menerapkan protokol kesehatan COVID-19.Kata kunci: COVID-19; kepatuhan; leaflet